Challenges of COVID-19 in children in low- and middle-income countries (2020)
As the coronavirus pandemic extends to low and middle income countries (LMICs), there are growing concerns about the risk of coronavirus disease (COVID-19) in populations with high prevalence of comorbidities, the impact on health and economies more broadly and the capacity of existing health systems to manage the additional burden of COVID-19. The direct effects of COVID are less of a concern in children, who seem to be largely asymptomatic or to develop mild illness as occurs in high income countries; however children in LMICs constitute a high proportion of the population and may have a high prevalence of risk factors for severe lower respiratory infection such as HIV or malnutrition. Further diversion of resources from child health to address the pandemic among adults may further impact on care for children. Poor living conditions in LMICs including lack of sanitation, running water and overcrowding may facilitate transmission of SARS-CoV-2. The indirect effects of the pandemic on child health are of considerable concern, including increasing poverty levels, disrupted schooling, lack of access to school feeding schemes, reduced access to health facilities and interruptions in vaccination and other child health programs. Further challenges in LMICs include the inability to implement effective public health measures such as social distancing, hand hygiene, timely identification of infected people with self-isolation and universal use of masks. Lack of adequate personal protective equipment, especially N95 masks is a key concern for health care worker protection. While continued schooling is crucial for children in LMICs, provision of safe environments is especially challenging in overcrowded resource constrained schools. The current crisis is a harsh reminder of the global inequity in health in LMICs. The pandemic highlights key challenges to the provision of health in LMICs, but also provides opportunities to strengthen child health broadly in such settings.